Взаимодействие параметрически возбуждаемого гибкого стержня с динамическим гасителем - Деревянко, Ю. С.; Аврамов, К. В. (НТУ "ХПИ", 2008)
У статті отримана динамічна система, яка описує параметричні коливання гнучкого стрижня. Взаємодія шарнірно обпертого гнучкого стрижня із динамічним гасителем описується дискретною моделлю із двома ступенями вільності. Представлено результати чисельного аналізу параметрично збуджуваної динамічної системи.

The dynamical system describing parametric vibrations of elastic beam is derived here. The interaction between a hinged-clamped elastic beam and attached mass-spring absorber is modelled by two-degree-of-freedom system. One-mode approximation of the beam oscillations is used. The results of numerical simulations of parametrically excited dynamical system are presented.
Keywords: динамические нагрузки; колебания; гибкий стержень; линейный гаситель колебаний; динамическая неустойчивость; метод Бубнова-Галеркина